Handbook of optical design - Malacara, Daniel, 1937-; Malacara, Zacarias, 1948- (Boca Raton, FL : CRC Press, 2013)
'Infused with more than 500 tables and figures, this reference clearly illustrates the intricacies of optical system design and evaluation and considers key aspects of component selection, optimization, and integration for the development of effective optical apparatus. The book provides a much-needed update on the vanguard in the field with vivid explanations of computer-aided strategies and developments essential for success in the engineering of modern optical structures. It analyzes the performance of a wide range of optical materials, components, and systems, from simple magnifiers to complex lenses used in photography, ophthalmology, telescopes, microscopes, and projection systems'--
Includes bibliographical references ( p. 531-532) and index.
Keywords: Lenses -- Design and construction -- Handbooks, manuals, etc; Mirrors -- Design and construction -- Handbooks, manuals, etc; Optical instruments -- Design and construction -- Handbooks, manuals, etc